Research on Theoretical Isuues of Word Formation in the Works of Manuk Abeghyan and Hrachya Acharyan - Nersisyan , Varsik (Bulletin of Yerevan University B: Philology, 2026)
Due to the need to carry out work aimed at systematizing the theory of synchronic word formation in Modern Armenian language, it becomes particularly important to refer to the views of various linguists who have worked in this field. This study attempts to fill research gaps in this field: based on descriptive-analytical approach the views of two prominent Armenian linguists, Manuk Abeghyan and Hrachya Acharyan, on issues of word formation are examined in general terms and the main similarities and differences are identified. Overall, it can be summarized that Abeghyan’s objective is not only studying the historical development of the Armenian vocabulary and identifying its patterns (in some cases also through comparison with similar phenomena in other languages, primarily Russian and German), but also their scientifically grounded analysis and systematization. In his works, it is difficult to differentiate between Abeghyan, the scholar and Abeghyan, the educator, since his theoretical analysis is organically combined with a purposeful teaching-methodological task and is accompanied by considerable efforts aimed at the systematic and coherent presentation of scientific material. In the case of Acharyan, the approach is different. He does not undertake the development of theoretical issues in word formation, a task that had already been comprehensively addressed by Abeghyan. His primary goal is identifying the patterns and structural features of word formation, as well as uncovering the relationships between them in various languages, particularly in the Armenian language.